(untitled) (Proceedings of Southern Federal University. Philology, 2015)
Gavrilova Galina Fedorovna, Zhukova Elena Alexandrovna This article analyzes the stylistic-syntactic features of a compound sentence in texts of the first stories by M.A. Sholokhov (1923-1926), it is considered their diversity in monologue and dialogue speech, polyfunctionality of their coherent means - coordinative conjunctions, which allowed the writer to avoid uniformity in the language of stories and deautomatize perception of the content by the reader, i.e. M.A. Sholokhov has already here distinguished himself as a mature artist, masterly using in artistic purposes the peculiarities of Russian syntax. Key words: text and its semantics, multifunctionality; compound sentences of homogeneous and inhomogeneous composition; flexible-inflexible structure, pseudoauthor.